PENGGUNAAN SAKSI MAHKOTA DALAM TINDAK PIDANA PENCURIAN YANG DISERTAI DENGAN KEKERASAN (STUDI KASUS NO 563/PID.B/2019/PN.JKT.BRT) - Ahmad Aryadi; R Rahaditya (Fakultas Hukum Universitas Tarumanagara, 2021)
This study aims to analyze the use of crown witnesses in criminal acts that often occur in the prosecution process in court as evidence in cases witnessed by the defendants, especially in cases of theft accompanied by violence. This research was conducted with a normative research approach and with data collection, one of which was by conducting interviews with the defendants and also their families as a data collection technique and also literature study obtained from the prevailing laws and regulations, books, jurisprudence of the Supreme Court, as well as Supreme Court Circular Letters, journals, and internet sites. The results of this study indicate that the use of crown witnesses in evidence in Indonesia is often used, initially the reason for using crown witnesses was as evidence against the public against the crime that occurred, but along with the times the crown witnesses should be accompanied by sufficient evidence to prove that the defendant is a people who are truly proven to have committed a criminal act, the need for legal protection related to the improvement of the Criminal Procedure Code, especially the affirmation of the use of crown witnesses, is needed, legal protection by providing an understanding of the human rights of people who have been harmed due to misunderstandings caused by the dualism of understanding of Jurisprudence as one a source of law that has permanent legal force, so that the purpose of law, namely to establish order and balance in society can be achieved.